Regional socio-economic determinants of the development of the bio-economy in agriculture - Piotr Kulyk; Anna Kowalewicz; Aleksandra Nowomiejska (Institute of Economic Research (IER), 2017)
Bio-economy regional level is essential for the socio-economic impact, especially in sparsely populated peripheral areas. The positive effects of bio-economy in the agro-food sector can be regarded as an increase in em-ployment and incomes and security of supply. The purpose of the article was to define and determine the potential of bio-economy in the polish Voivodships. In addition, it attempts to define the role of bio-economy in the agro-food sector, including the environmental aspects. The study covered the period 2005-2015. In order to assess the influence of macroeconomic factors on the development of sustainable agriculture the article used method of panel analysis with fixed effects. The data for the analysis was taken from the statistical data from the Local Data Bank (BDL), the Central Statistical Office and the Chief Inspectorate of Trade Quality of Agricultural and Food (GIJHARS). In order to increase the potential of the region it is necessary to recognize the im-portance of local knowledge as a stimulant of competitiveness of regional devel-opment, while taking into account the diversity and complexity of local systems. In order to improve opportunities for bio-economy and green growth it is necessary to better understand the role of natural capital and related changes.The integration of cross-sectoral dimensions of ecological, social-cultural and socio-economic development in the process of regional management is becoming important. In this context, there is a need for further study of the so-cio-economic conditions to determine the regional conditions providing a perma-nently sustainable development with the use of bio-economy in agriculture.
Keywords: O13; Q01; 330; bio-economy; local development; economic and social determinants; the Lubuskie Voivodeship; sustainable agriculture